Longer physical exercise duration prevents abnormal fasting plasma glucose occurrences in the third trimester: Findings from a cohort of women with gestational diabetes mellitus in Shanghai - Zhang, Rui; Gao, Xiangjin; Sun, Ting; Li, Huan; Yang, Qing; Li, Bin; Zhu, Dongshan; Wang, Ruiping (Frontiers in Endocrinology, 2023)
Objective: To explore the association between daily physical exercise (PE) duration and frequency of abnormal PG times in women with gestational diabetes mellitus (GDM). Methods: We established a cohort involving 878 GDM women. GDM was confirmed by a diagnostic 75g oral glucose tolerance test (OGTT). Information was extracted from the delivery records and antenatal checkup forms. Physical exercise information was collected through questionnaire. Results: Over 80% of GDM women were under 35 years. An abnormal PG (plasma glucose), with ≥4 occurrences was present in 365/878 (41.57%). Compared to GDM women with ≥4 occurrences of abnormal fasting PG, GDM women with zero occurrence [odds ratio(OR)=2.56], 1 occurrence [OR=1.94], 2 occurrences [OR=2.29] and 3 occurrences [OR=2.16] had higher proportion of PE duration being in 45-60 minutes/ day group than those in <45 minutes/day group, and GDM women also had higher proportion of PE during being in 61-90 minutes/day group, > 90minutes/day group than those in <45 minutes/day group. Whereas, PE duration was not associated with numbers of abnormal PG occurrence 2-h after standard diet. Conclusion:Moderate intensity PE duration among GDM women was negatively correlated with the number of abnormal PG occurrence after the fasting test, but not the PG occurrence 2-h after standard diet.